(untitled) (Innovative professional education, 2025)
The article examines the ways to develop the subjectivity of public-private partnership participants in ensuring the quality of vocational education based on the findings of the study «Trends in the Development of Public-Private Partnership in the Field of Vocational (Vocational-Technical) Education». Special attention is given to the importance of creating and implementing relevant scientific, informational, and educational-methodological support, the effectiveness of disseminating best practices of partnership interaction during scientific and practical events, and the impact of professional development for administrators and teaching staff of vocational education institutions.